2000
DOI: 10.1063/1.1150182
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentation for millimeter-wave magnetoelectrodynamic investigations of low-dimensional conductors and superconductors

Abstract: We describe instrumentation for conducting high sensitivity millimeter-wave cavity perturbation measurements over a broad frequency range (40 − 200 GHz) and in the presence of strong magnetic fields (up to 33 tesla). A Millimeter-wave Vector Network Analyzer (MVNA) acts as a continuously tunable microwave source and phase sensitive detector (8 − 350 GHz), enabling simultaneous measurements of the complex cavity parameters (resonance frequency and Q−value) at a rapid repetition rate (∼ 10 kHz). We discuss the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
153
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(154 citation statements)
references
References 21 publications
1
153
0
Order By: Relevance
“…We have also ignored hyperfine effects, since these are irrelevant in the case of the Fe 8 Br ( 56 Fe has no nuclear spin), and exchange narrowing in Mn 12 −ac is believed to diminish the hyperfine splitting [37]. At present, most of our data have been obtained for [28,52]) yields crystal field parameters that are in much closer agreement with inelastic neutron scattering measurements than conventional high field EPR studies [61].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…We have also ignored hyperfine effects, since these are irrelevant in the case of the Fe 8 Br ( 56 Fe has no nuclear spin), and exchange narrowing in Mn 12 −ac is believed to diminish the hyperfine splitting [37]. At present, most of our data have been obtained for [28,52]) yields crystal field parameters that are in much closer agreement with inelastic neutron scattering measurements than conventional high field EPR studies [61].…”
Section: Discussionsupporting
confidence: 71%
“…refs [8,31,32,33,34]). Careful consideration concerning the coupling of radiation to and from the cavity (via waveguide), combined with the ability to study very small samples, eliminates problems associated with standing waves in the sample probe [52]. This, in turn, eliminates a mixing of the dissipative and reactive responses of the sample under investigation and, when combined with a vector detection scheme, enables faithful extraction of the true EPR lineshapes (both the real and imaginary components), free from instrumental artifacts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high degree of sensitivity required for single-crystal measurements is achieved using a resonant cavity perturbation technique in combination with a broad-band Millimeter-wave Vector Network Analyzer (MVNA) exhibiting an exceptionally good signal-to-noise ratio; a detailed description of this instrumentation can be found in Ref. [27]. The MVNA is a phase-sensitive, fully sweepable (8 Á/350 GHz), superheterodyne source/detection system.…”
Section: Methodsmentioning
confidence: 99%
“…Inelastic neutron scattering [19] and high-frequency EPR studies [8,20] of powder samples have shown the need to include higher-order terms (fourth-order in the spin operators) in the above Hamiltonian; these terms are important, because they may provide clues as to the mechanism of the quantum tunneling phenomenon. However, the neutron and EPR studies published to date do not agree on the magnitudes of the higher-order Hamiltonian terms, or even on the exact D and E parameters [8,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%